Artificial intelligence and productivity: Global evidence from AI patent and bibliometric data - Aleksandra Parteka; Aleksandra Kordalska (Gdańsk University of Technology, Faculty of Management and Economics, 2022)
In this paper we analyse the effects of technological innovation in the artificial intelligence (AI) domain on productivity. We embed the recently released data on patents and publications related to AI into an augmented panel model of productivity growth, estimated for OECD countries, and compared to a non-OECD sample. Our instrumental variables' estimates, accounting for AI endogeneity, provide evidence in favour of the modern (AI) productivity paradox. We show that the development of AI technologies remains a niche innovation phenomenon with a negligible role in the officially recorded productivity growth process. This general result, i.e. the lack of a strong relationship between AI and productivity growth, is robust to changes in the country sample, in the way we quantify labour productivity or the creation of AI technology, in the specification of the empirical model (control variables) or in estimation methods.
Keywords: O33; O47; 330; technological innovation; productivity paradox; productivity growth; artificial intelligence; patents